The Use of Multimedia in Learning the Material of Movement in Plants in Class VIII MTsN Rukoh Banda Aceh - Yassir, Muhammad; Muhammad Tahir; Erlia Hanum (Journal Informatic, Education and Management (JIEM), 2025)
The topic of movement in plants is material that is taught in junior high schools in class II semester 2. Meanwhile, when the teacher explains the subject matter, students do not respond to the material taught by the teacher. The formulation of the problem in this research is how students respond at MTsN Rukoh Banda Aceh to the use of multimedia on the subject of movement in plants in class VIII MTsN Rukoh Banda Aceh City. This research aims to determine the response of MTsN Rukoh Banda Aceh students to the use of multimedia on the subject of movement in plants. For this reason, the author took the subjects of this research in class II3 MTsN Rukoh Banda Aceh as many as 23 people. The data collection procedure is through distributing questionnaires to students. Meanwhile, data analysis techniques use simple statistics or percentages. The results of the research showed that the majority of students gave a positive response to learning using multimedia on movement material on plants as a whole was categorized as good. Thus, the teaching and learning process (PBM) using multimedia on movement material on plants was generally positive.